Banff Human Organ Transplant Transcripts Correlate with Renal Allograft Pathology and Outcome: Importance of Capillaritis and Subpathologic Rejection. Issue 12 (December 2022) - Rosales, Ivy A.; Mahowald, Grace K.; Tomaszewski, Kristen; Hotta, Kiyohiko; Iwahara, Naoya; Otsuka, Takuya; Tsuji, Takahiro; Takada, Yusuke; Acheampong, Ellen; Araujo-Medina, Milagros; Bruce, Amy; Rios, Andrea; et al.
Significance Statement: Microarray analysis of renal allograft biopsies has revealed important insights, including TCMR and AMR gene sets, but is limited to specially processed samples without pathology confirmation. We used the NanoString nCounter platform to perform mRNA analysis of archived formalin-fixed paraffin-embedded kidney allograft biopsies with the Banff Human Organ Transplant Panel. We correlated Banff pathology scores in the same tissue block with validated and custom gene sets and showed the importance of capillaritis. We identified subpathological transcripts that standard pathology would not have detected and transcripts, pathology, and clinical variables that predicted graft failure in TCMR and CAMR. These findings highlight the utility of archived samples in transplant pathology research and expand our understanding of the pathogenesis of rejection. Visual Abstract: Abstract : Background: To seek insights into the pathogenesis of chronic active antibody–mediated rejection (CAMR), we performed mRNA analysis and correlated transcripts with pathologic component scores and graft outcomes. Methods: We utilized the NanoString nCounter platform and the Banff Human Organ Transplant gene panel to quantify transcripts on 326 archived renal allograft biopsy samples. This system allowed correlation of transcripts with Banff pathology scores from the same tissue block and correlation with long-term outcomes. Results: The only pathology score that correlated with AMR pathways in CAMR was peritubular capillaritis (ptc). C4d, cg, g, v, i, t, or ci scores did not correlate. DSA-negative CAMR had lower AMR pathway scores than DSA-positive CAMR. Transcript analysis in non-CAMR biopsies yielded evidence of increased risk of later CAMR. Among 108 patients without histologic CAMR, 23 developed overt biopsy-documented CAMR within 5 years and as a group had higher AMR pathway scores ( P =3.4 × 10 –5 ). Random forest analysis correlated 3-year graft loss with elevated damage, innate immunity, and macrophage pathway scores in CAMR and TCMR. Graft failure in CAMR was associated with TCMR transcripts but not with AMR transcripts, and graft failure in TCMR was associated with AMR transcripts but not with TCMR transcripts. Conclusions: Peritubular capillary inflammation and DSA are the primary drivers of AMR transcript elevation. Transcripts revealed subpathological evidence of AMR, which often preceded histologic CAMR and subpathological evidence of TCMR that predicted graft loss in CAMR.